Contextos variables, categorías estables y nociones divergentes: reflexiones sobre la investigación de la cuestión social en la Argentina de los 90 - Gabriel Kessler (Cahiers des Amériques Latines)
The paper presents the debates on poverty, and in general on the «social question» in Argentina experiencing a rapid social change due to the drastic application of the neo-liberal reforms during the ninties. First, it shows how the «new poverty» which has not been examined in relation with politics challenged the official categorizations used till then; secondly, it questions in a comparative perspective the latino-american intellectual tradition, namely the tradition of «moral ecomomy» theories, and the european school of thought, such as the theory of «desaffiliation»; lastly, it discusses the influence of the schemes of analysis proposed by the international institutions financing social policy projects and related research.